Charting the Course of Active Learning Methods Research: A Comprehensive Bibliometric Analysis - Nurul Latifatul Inayati; Vanneza Diva Ariona (Didaktika: Jurnal Kependidikan, 2023)
The purpose of this study was to describe the development map and research direction of active learning methods in publications indexed by the Scopus database. The technique in this study was to use bibliometric analysis to review all publications indexed in the Scopus database about active learning methods starting from 2000 to 2024. The data that has been obtained, is then analyzed using Microsoft Excel and R/R-Studio. VOSviewer is used to visually analyze the occurrence of keywords and document excerpts done stimulantly. The author finds 318 publications. Publications found correspond to predetermined subjects, functions, and criteria. The results of this study show that research with the theme of active learning methods was mostly carried out in 2020. The country that contributes to having the most publications is China, then in second place is the United States. The Sharif University of Technology is the highest affiliate with the most influence in publishing research on the theme. Shouraki, S.B. is the most relevant author. Iee Access is the most widely published writing source on active learning methods. The bibliometric analysis performed was limited to the Scopus database. Other national and international databases were not taken into account in the study. This study provides an overview of the literature available to researchers in the field of education and recommendations for future research.